High performance real-time vision system for robot guidance - Xie, Ming. (2008)
This report highlights the main research results done on the Applied Research Project ARC 1/94 entitled "High Performance Vision System for Robot Guidance". The principal objective of this project is to explore the use of emerging technology on active vision and parallel computing to develop a high performance real-time vision system which is both powerful and complete to enable practical guidance of robotic systems such as assembly robot or mobile vehicle.